Comparison of the safety profiles for pirfenidone and nintedanib: a disproportionality analysis of the US food and drug administration adverse event reporting system - Sun, Xiangyu; Wang, Huaguang; Zhan, Xi; Yan, Yuanyuan; Chen, Kun; An, Zhuoling; Zhou, Hong (Frontiers in Pharmacology, 2024)
Background: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive interstitial lung disease of unknown etiology. Pirfenidone (PFD) and nintedanib (NDN) were both conditionally recommended in the clinical practice guideline published in 2015.Safety and tolerability are related to the risk of treatment discontinuation. Therefore, this study evaluated and compared the adverse events (AEs) of PFD and NDN in a large real-world population by analyzing data from the FDA Adverse Event Reporting System (FAERS) to provide a reference for their rational and safe use.The AEs of PFD and NDN were extracted from the FAERS database. The pharmacovigilance online analysis tool OpenVigil 2.1 was used to retrieve data from the FAERS database from the first quarter of 2012 to the second quarter of 2022. The reporting odds ratio (ROR) and proportional reporting ratio were used to detect the risk signals.The database included 26,728 and 11,720 reports for PFD and NDN, respectively. The most frequent AEs of PFD and NDN were gastrointestinal disorders.The RORs for these drugs were 5.874 and 5.899, respectively. "Cardiac disorders" was the most statistically significant system order class for NDN with an ROR of 9.382 (95% confidence interval = 8.308-10.594). Furthermore, the numbers of designated medical events of PFD and NDN were 552 and 656, respectively. Notably, liver injury was reported more frequently for NDN (11.096%) than for PFD (6.076%).This study revealed differences in the reporting of AEs between PFD and NDN. The findings provide reference for physicians in clinical practice. Attention should be paid to the risks of cardiac disorders and liver injury associated with NDN.